The Effect of Board Diversity on Carbon Emission Disclosure - Rahmawati, Rizkika Putri; Wijayanti, Rita; Ariani, Kurnia Rina (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: Climate change has emerged as a growing concern on a global scale, prompting organizations to prioritize carbon-friendly practices. There is a growing call for businesses to actively reduce carbon emissions by implementing initiatives in their operational processes. The Indonesian government pays great attention to the issue of global climate change. This can be seen from the 17 sustainable development goals, climate change is one of the goals that is starting to be socialized. Rising global temperatures result from heightened levels of greenhouse gas emissions released into the atmosphere, so companies must take responsibility through emission reduction activities. Disclosure of carbon emissions is to assess carbon emissions in order to set targets for reducing these emissions. This study seeks to assess how effectively climate change has been tackled and the various factors that contribute to the tampering of data on carbon emissions. The factors tested in this research include other female directors, foreign directors, and independent directors. Metodology: The study involves examining annual non-financial firms that are listed on the Indonesia Stock Exchange (IDX) have reported between 2020 - 2022 using content analysis. Quantitative methods are employed, and samples are selected through purposive sampling techniques. The hypothesis testing is conducted using SPSS 25, and the analysis involves the application of the multiple linear regression model. Result: According to the study's findings, disclosure of carbon emissions is positively impacted by board independence, diversity in nationality, and profitability. However, disclosure of carbon emissions is unaffected by corporate size, leverage, or gender diversity on the board. Applications/Originality/Value: The study makes a meaningful contribution to the advancement of green accounting in Indonesia, with the aspiration that stakeholders can enhance their evaluation and planning processes to augment carbon emission disclosure by companies in the country.